Recommendations for the management of the variable "students" on the road to excellence - José Osvaldo Enríquez Clavero; Eusebio Pardillo Rodríguez; Belkis García Cárdenas; Maritza Canto Pérez; Olga Lidia Véliz Concepción (Editorial Ciencias Médicas, 2015)
Accreditation is the process by which the quality of the university studies evaluated is publicly recognized (or certified). Little has been published about the results and experiences of university studies undergoing such a process. It is our purpose to share with colleagues some recommendations for the management of the variable "students" based on the lessons learned along two accreditation processes conducted at the School of Dentistry in Villa Clara. A bibliographic review was conducted in the database ScieLO Cuba. The review included self-evaluation reports and all the work documents of the subcommittee in charge of the variable "students". For self-evaluation of university studies, the Evaluation and Accreditation System has instructed the creation of a commission and five subcommissions, one for each variable. It is recommended that the subcommission for the variable "students" should have an appropriate composition, examine self-evaluation reports from other schools, and develop records or databases with the participation and results of students in the various activities. With respect to the preparation of students for the external inspection, it is recommended to organize informative meetings, as well as instruct students about the objectives of the group interview, the integrating examinations and the work with the artistic talent. Based on the notion that excellence is the result of a permanent self-evaluation process, some suggestions or recommendations are presented for the management of this variable as regards the development of the self-evaluation report and the preparation of students for the external inspection. All this stems from the experience accumulated by a school which has undergone two accreditation processes.